Avaliação da satisfação e qualidade de vida dos pacientes usuários de próteses sobre implantes (protocolo e overdenture) desenvolvidas em instituições de ensino odontológico públicas e privadas - Braga, Michelle (2007)
The patient satisfaction is a relevant aspect that actually matters with regards to the success of the treatment. And it is also so important that it must be regarded as an imperative outcome parameter.Considering the lack of scientific studies about patient satisfaction variables and oral health–related quality of life in implant supported prothesis therapy (protocol and overdenture). Based on these concerns, the aim of this study is to evaluate the satisfaction and oral health-related quality of life in patients with fixture-retained prostheses (protocol and overdenture); then to establish comparisons between groups (protocol and overdenture) and intra-group (bar-clip and individual retainers) comparisons that were held in implant postgraduate courses of private and public institutions. This paper is a cross-sectional study and the patient selection was based on data from the patients’ files from private and public institutions. The sample consisted of 35 subjects, including males and females, with age ranging from 43 to 77, treated with implant-anchored full prostheses in the last 4 years. Fifteen patients had implant-retained complete prostheses, 19 patients had implant-supported overdentures, and from these 20, 12 had bar-clip retainers and 8 had individual retainers. The patient satisfaction variables and oral health-related quality of life were assessed through self-questionnaires and a short form of the Oral Health Impact Profile (OHIP-14). The data were gathered and estimated in a database customized specifically for the research using Windows Excel and the statistical analyses were made by SPSS for Windows (13.0). The Kruskall-Wallis test (non-usual distribution of researched data) was used and the Cronbach’s α was used for checking the reliability of the instruments. In conclusion, there were no significant statistical differences between Protocol and Overdenture groups regarding the following variables: comfort and retention; stability; prosthesis grade; esthetics; oral discomfort; functional restrictions; phonetics limitations; social limitations; and psychological discomfort (p > 0,050). Nevertheless, the group including patients treated with complete prostheses fixed by implants showed higher satisfaction scores compared to the group including patients treated with overdentures supported by implants (p = 0,049 < 0,05). In view of the oral health-related quality of life measured by OHIP-14, the overdenture group showed low impact considering functional limitation and low scores when comparing protocol group. There were no significant statistical differences in the intra-group comparisons (bar-clip retainer and individual retainer).